The Difficulties in Creating Transactional and Interpersonal Conversations by Students of SMPN 2 Padang - Prih Febtiningsih; Siti Niah; Ardiya Ardiya (Faculty of Teacher Training and Education, 2019)
This study aimed to determine what difficulties faced by the students at SMP Negeri 2 Padang in transactional and interpersonal conversations, namely difficulties in using grammatical competence and sociolinguistic competence. In this study, researchers chose the second-year students of SMP Negeri 2 Padang as the population. The samples in this study were students of class VIII.4, consisting of 36 students based on cluster sampling techniques. The instruments used were observation and interview. The researchers observed some difficulties that happened when the students created transactional and interpersonal conversations with their partners in front of the class using an observation checklist. After making observations, researchers interviewed the students to find out the causes of these difficulties. From the observations, the researchers found that 55.65% of students had difficulties in using grammatical competence, namely in grammar, vocabulary and pronunciation. 66.67% of students have difficulties in using sociolinguistic competence (the use of speech acts). Based on the results of the interview, it was found that the factors that caused students to have difficulties in using grammatical competence were lack of grammatical knowledge due to lack of practice, lack of classroom management control by the teacher so that noisy classes made students pay less attention to the teacher's explanation when explaining the lesson. The teacher also did not give motivation to students to review the lessons that have been taught so that they rarely relearned at home. In addition, many teachers used English so students did not understand what the teacher said. Another factors were rush, forgetfulness, carelessness, nervousness, hesitation, and inattentiveness. The factors that caused students to have difficulties in using sociolinguistic competence were the lack of knowledge of using speech acts, forgetting, and not knowing what the other person said. Thus, it could be concluded that the students of SMPN 2 Padang have difficulties in transactional and interpersonal conversations, namely difficulties in using grammatical competence and sociolinguistic competence. Keywords: difficulties, transactional and interpersonal conversation